A novel model to manage air cargo disruptions caused by global catastrophes such as Covid-19. (August 2021) - Shaban, Ibrahim Abdelfadeel; Chan, F.T.S.; Chung, S.H.
Abstract: The outbreak of the COVID-19 pandemic has drastically disrupted the air cargo industry. This disruption has taken many directions, one of which is the demand imbalance which occurs due to the sudden change in the cargo capacity, as well as demand. Therefore, the random change leads to excessive demand in some routes (hot-selling routes), while some other routes suffer from a big shortage of demand (underutilized routes). Routes are substitutable when there are several adjacent airports in the Origin & Destination (O&D) market. In this market, demand imbalance between substitutable routes occurs because of the above reasons. To tackle the demand imbalance problem, a novel model is introduced to estimate the quantity combinations which maintains the balance between underutilized and hot-selling routes. This model is a variant of the classic Cournot model which captures different quantity scenarios in the form of the best response for each route compared to the other. We then cultivate the model by integrating the Puppet Cournot game with the quantity discount policy. The quantity discount policy is an incentive which motivates the freight forwarders to increase their orders in the underutilized routes. After conducting numerical experiments, the results reveal that the profit can increase up to 25% by using the quantity discount. However, the quantity discount model is only applicable when the profit increase in the hot-selling route is greater than the profit decrease in the underutilized route. Highlights: The Puppet Cournot is proposed to fix the imbalance between two air freight routes. An airline acts as a puppeteer to control the full game between the two routes. The quantity discount policy is integrated with the Puppet Cournot game model. The best responses of the two routes represent the balancing scenarios between them. The quantity discount policy is limited, when it is integrated with the Puppet Cournot.